Effect of aqueous extract of Simarouba versicolor on Sitophilus zeamais (Coleoptera: Curculionidae) in laboratory (Research, Society and Development, 2022)
The use of synthetic insecticides in the management of Sitophilus zeamais has caused problems, such as the selection of resistant insects, making the search for less aggressive control strategies desirable. Simarouba versicolor is a plant native to Brazil, with insecticidal properties. Due to the lack of information on the action of S. versicolor on stored grain pests, the effect of S. versicolor on S. zeamais adults was evaluated. The lethal effect was evaluated by direct and residual exposure to leaf extract of S. versicolor at concentrations of 0.1% and 0.01%, distilled water (negative control) and Citromax® at 0.1% concentration (positive control)). The sublethal effect was evaluated through population development parameters (ri) of the weevil in corn previously exposed to different treatments and repellency was verified in free-choice tests. Direct contact with S. versicolor caused a low mortality of S. zeamais. Mortality caused by Citromax® was 72.7% higher than that observed for S. versicolor 24h after exposure. Residual contact with S. versicolor and Citromax® caused a low mortality of S. zeamais. In evaluations after 120h the mortality caused by S. versicolor did not exceed 5.0%, while for Citromax® the mortality was 5.4%. The population of S. zeamais exposed to distilled water had the highest ri (0.014), being ≈ 28.5% higher than the ri of the populations of S. zeamais exposed to S. versicolor. Citromax® had a negative ri, indicating the probable extinction of the population. S. versicolor did not show repellent activities.